Templated growth of PFO-DBT nanorod bundles by spin coating: effect of spin coating rate on the morphological, structural, and optical properties - Fakir, M.S.; Supangat, A.; Sulaiman, K. (SpringerOpen, 2014)
In this study, the spin coating of template-assisted method is used to synthesize poly[2,7-(9,9-dioctylfluorene)-alt-4,7-bis(thiophen-2-yl)benzo-2,1,3-thiadiazole] (PFO-DBT) nanorod bundles. The morphological, structural, and optical properties of PFO-DBT nanorod bundles are enhanced by varying the spin coating rate (100, 500, and 1,000 rpm) of the common spin coater. The denser morphological distributions of PFO-DBT nanorod bundles are favorably yielded at the low spin coating rate of 100 rpm, while at high spin coating rate, it is shown otherwise. The auspicious morphologies of highly dense PFO-DBT nanorod bundles are supported by the augmented absorption and photoluminescence.